APPLICATION OF USER-CENTERED DESIGN IN DAYSCADY APPLICATION DEVELOPMENT FOR DAILY ACTIVITY SCHEDULE MANAGEMENT - Aulia, Revina; Hardiwibowo, Restu Agung (Deparment Information System, Siliwangi University, 2024)
This study aims to evaluate the effectiveness of the Dayscady application, a daily schedule management tool designed using a user-centred design (UCD) approach. The application focuses on meeting user needs by providing a streamlined interface and personalised scheduling features. Twenty respondents participated in this research, providing insights into usability and potential improvements. The study used a mixed methods approach, combining quantitative surveys and qualitative interviews. Respondents completed a Likert-scale questionnaire to assess usability, satisfaction and functionality, and participated in interviews to provide detailed feedback. Quantitative results showed that 90% of respondents were willing to use the application regularly. However, qualitative feedback highlighted areas for improvement, including a desire for more dynamic interactions through pop-up features, clearer notifications and a comprehensive guide for new users. These findings demonstrate the potential of Dayscady to significantly improve user productivity by addressing their schedule management needs. The findings also highlight the importance of continuous iteration in application development, particularly in refining the user experience and functionality based on feedback. For future research, it is recommended to investigate the long-term impact of the application on productivity and to increase the sample size in order to draw more generalised conclusions. In addition, incorporating gamification elements or integrating AI-driven recommendations could further enhance the effectiveness and engagement of the application. This study provides a basis for optimising Dayscady and contributes to the advancement of user-centred application design.